2004
DOI: 10.1007/s11664-004-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Creep behavior of the ternary 95.5Sn-3.9Ag-0.6Cu solder: Part II—Aged condition

Abstract: Compression creep tests were performed on the 95.5Sn-3.9Ag-0.6Cu (wt.%) solder. The specimens were aged prior to testing at 125°C, 24 h or 150°C, 24 h. Applied stresses were 2-40 MPa. Test temperatures were Ϫ25°C to 160°C. The 125°C, 24-h aging treatment caused the formation of coarsened Ag 3 Sn particle boundaries within the larger ternary-eutectic regions. The 150°C, 24-h aging treatment resulted in contiguous Ag 3 Sn boundaries in the ternary-eutectic regions as well as a general coarsening of Ag 3 Sn parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 13 publications
5
28
0
Order By: Relevance
“…Incidentally, the stress exponent values in our study are comparable to the range of stress exponents (n = 7 to 4) and (n = 8 to 4) obtained, respectively, in bulk tension samples of Sn-3.9Ag-0.6Cu (from À25°C to 160°C) 22,23 and Sn-3.5Ag-(0 to 1.5)Cu (at 100°C). 24 The results in this study also reveal the same observation as reported by other researchers, [22][23][24] in that increasing temperature leads to decreasing stress exponent (n). It is well established that the applied stress and the testing temperature are factors influencing creep.…”
Section: Indentation Creep At Elevated Temperaturesupporting
confidence: 90%
“…Incidentally, the stress exponent values in our study are comparable to the range of stress exponents (n = 7 to 4) and (n = 8 to 4) obtained, respectively, in bulk tension samples of Sn-3.9Ag-0.6Cu (from À25°C to 160°C) 22,23 and Sn-3.5Ag-(0 to 1.5)Cu (at 100°C). 24 The results in this study also reveal the same observation as reported by other researchers, [22][23][24] in that increasing temperature leads to decreasing stress exponent (n). It is well established that the applied stress and the testing temperature are factors influencing creep.…”
Section: Indentation Creep At Elevated Temperaturesupporting
confidence: 90%
“…However, the coarsening of Ag 3 Sn particles is relatively slow because it is a covalently bonded compound. 21 A high activation energy is required to break the covalent bonds in the particles in order to allow Ag to diffuse toward growing particles. At the aging temperature of 150°C, the solubility of Bi in Sn is around 18 wt.%.…”
Section: Microstructure and Microhardness Of Sn-ag-xbi Soldersmentioning
confidence: 99%
“…For example, in terms of D o , the Sn grain size changes very little with typical annealing treatments at 150°C (e.g., 1 h to 24 h). 30,31 Concurrently, the Sn whisker density did not change significantly as a consequence of the annealing treatment. 31 A similar observation was made by Cheng et al on evaporated Sn films ($1 lm grain size).…”
Section: Tin (Sn) Whisker Growth Model By Dynamic Recrystallizationmentioning
confidence: 96%